Generation of spectrum-compatible ground motion records based on time-frequency decomposition. Issue 161 (October 2022) - Mo, H.M.; Cui, X.Z.; Hong, H.P.
Abstract: Spectrum-matched records are used in seismic engineering applications. The available approaches in the literature are based on the Fourier transform or wavelet transform. In the present study, we propose a novel and easy-to-implement approach to generate spectrum-matched records for a given seed record. The approach is based on the S-transform (ST). The use of the transform is advantageous since they provide refined time-frequency decomposition. The approach adjusts the amplitude of the ST coefficients in the S-transform domain. The approach is effective in matching a prescribed response spectrum at specified frequencies without complex parameter adjustment. The spectrum-matched records qualitatively retain the look of the seed records. The spectral acceleration of the spectrum-matched records is equal to the target spectrum at the specified frequencies, where the matching is required and specified. Highlights: We proposed a new novel and easy to implement approach to generate spectrum-matched records for given seed records. We showed the adequacy of the approach in reproducing the target smoothed or non-smoothed design spectrum. We illustrated the obtained spectrum-matched records retain the look of the seed records. We compared the performance of our proposed approach and a well-known approach in obtaining the spectrum matched records.